Pengembangan Lembar Kerja Peserta didik Berbasis Sosial Budaya Dalam Memahami Materi Cerita Pendek Untuk Meningkatkan HOTS Siswa Kelas XI SMA - Vannisa Hidayasa; Liesna Andriany; Amaluddin (Medan Resource Center, 2022)
This study aimed to develop socio-cultural-based LKPD teaching materials in understanding short story material to improve HOTS for class XI SMA. The research method used 4-D Research and Development by Thiagarajan that consists of four stages, namely define, design, development, and dissemination. This study is limited to the development stage, due to the current pandemic situation so it cannot be carried out for the dissemination stage. Data was collected using research instrument techniques to assess the validity of the products that have been developed, in the form of a validation questionnaire to be assessed by material experts in the form of content, construction, language aspects and design experts in the form of writing display aspects, image display, LKPD functions, and LKPD benefits. The assessment of the material aspect got an overall score of 90% with the